PROJECT OF E-LEARNING MATERIAL DEVELOPMENT - RESETOVA, Kvetoslava (Trends in education, 2008)
The article deals with possibilities of the learning texts development in an accessible electronic form. It describes sources and the solution stages of the project that was carried out in an academic environment.
Keywords: electronic publishing; publishing activity; learning texts